2020
DOI: 10.3390/jcm9092951
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology and Psychopathology Underlying PTSD and Recent Insights into the PTSD Therapies—A Comprehensive Review

Abstract: Post-traumatic stress disorder (PTSD) is a well-known psychiatric disorder that affects millions of people worldwide. Pharmacodynamic and cognitive-behavioral therapies (CBT) have been used to treat patients with PTSD. However, it remains unclear whether there are concurrent changes in psychopathological and neurophysiological factors associated with PTSD patients. Past reports described those PTSD patients with efficient fatty acid metabolism, neurogenesis, mitochondrial energy balance could improve ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 130 publications
0
30
0
1
Order By: Relevance
“…All these findings would suggest that these miRNAs are part of a complex transcriptional and post-transcriptional machinery that controls fundamental processes in neurons and, consequently, their dysregulation would contribute to molecular cascades induced by neuropsychological stress. Moreover, enrichment analysis of miR-15a-5p, miR-497a-5p, miR-511-5p, and let-7d-5p network showed that such miRNA circuits could affect multiple cellular and molecular processes associated with PTSD pathogenesis [ 47 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Based on these considerations, the inverse correlation between arousal score and hippocampal expression of miR-15a-5p and miR-511-5p is not surprising, as it suggests the existence of a linear relationship between the behavioral arousal score of mice and miRNA levels in the brain that, in turn, coherently influences BDNF and FKBP5 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings would suggest that these miRNAs are part of a complex transcriptional and post-transcriptional machinery that controls fundamental processes in neurons and, consequently, their dysregulation would contribute to molecular cascades induced by neuropsychological stress. Moreover, enrichment analysis of miR-15a-5p, miR-497a-5p, miR-511-5p, and let-7d-5p network showed that such miRNA circuits could affect multiple cellular and molecular processes associated with PTSD pathogenesis [ 47 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Based on these considerations, the inverse correlation between arousal score and hippocampal expression of miR-15a-5p and miR-511-5p is not surprising, as it suggests the existence of a linear relationship between the behavioral arousal score of mice and miRNA levels in the brain that, in turn, coherently influences BDNF and FKBP5 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…One potential biomarker that could be useful in the assessment of individual stress is trimethylamine-N-oxide (TMAO). This gut bacteria-derived metabolite is an important cardiovascular risk marker that appears to interfere with many important physiological regulatory pathways (Aliev et al, 2020 ; Giannoni-Pastor, Eiroa-Orosa, Fidel Kinori, Arguello, & Casas, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adults in particular, biological underpinnings of PTSD have been demonstrated, which involve the hypothalamus-pituitary-adrenal (HPA) axis, neural circuitry of the limbic system, especially the amygdala, the prefrontal cortex, and the hippocampus, and its connections to the parahippocampal gyrus, orbitofrontal cortex, sensorimotor cortex, thalamus, and anterior cingulate cortex. The neuropathological findings in PTSD reflect excessive activation of the amygdala coupled with an underactive medial prefrontal cortex coupled with insufficient inhibition of strong responses to threat of danger from the amygdala [ 70 , 71 , 72 , 73 ]. Biological correlates of child disaster outcomes have also been considered [ 74 ].…”
Section: Discussionmentioning
confidence: 99%